2014
DOI: 10.2214/ajr.13.11797
|View full text |Cite
|
Sign up to set email alerts
|

MRI of Lymphatic Abnormalities After Functional Single-Ventricle Palliation Surgery

Abstract: Lymphatic abnormalities are found in many patients after functional single-ventricle palliation. T2-weighted unenhanced MRI is capable of anatomic assessment of the lymphatic system in this patient population and has promise for guiding treatment in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 14 publications
2
104
1
Order By: Relevance
“…Having significant gastrointestinal pathology may also, when compounded with single ventricle physiology, lead to abnormal stool A1AT samples, as the one subject with surgical repair of trachoesophageal fistula and necrotizing enterocolitis had an abnormal stool A1AT sample. Our findings support the hypothesis that children with single ventricle type of congenital heart disease may have inherently altered intestinal physiology, perhaps due to decreased cardiac output and splanchnic perfusion or due to abnormal intestinal lymphatics either as part of the congenital malformation itself or acquired during early palliative intervention (13). We hypothesize that children with single ventricle type of congenital heart disease remain in a state of acute compensation, even before Fontan operation.…”
Section: Commentsupporting
confidence: 85%
“…Having significant gastrointestinal pathology may also, when compounded with single ventricle physiology, lead to abnormal stool A1AT samples, as the one subject with surgical repair of trachoesophageal fistula and necrotizing enterocolitis had an abnormal stool A1AT sample. Our findings support the hypothesis that children with single ventricle type of congenital heart disease may have inherently altered intestinal physiology, perhaps due to decreased cardiac output and splanchnic perfusion or due to abnormal intestinal lymphatics either as part of the congenital malformation itself or acquired during early palliative intervention (13). We hypothesize that children with single ventricle type of congenital heart disease remain in a state of acute compensation, even before Fontan operation.…”
Section: Commentsupporting
confidence: 85%
“…4 Dynamic contrast-enhanced magnetic resonance lymphangiogram (DCMRL) has recently been described as a method of imaging the central lymphatic system. 15, 16 Dori et al 16,17 have recently reported on the use of this technique and T2-weighted MRI to characterize lymphatic abnormalities in patients with PB.…”
Section: Clinical Perspective On P 1170mentioning
confidence: 99%
“…We presented one patient with resolution of symptoms after catheter-based oil and glue embolization of lymphatic collaterals originating from the thoracic duct [25]. Increased understanding of the Fontan lymphatic system and its alterations under elevated central venous pressure is necessary and may be possible with novel MRI imaging techniques [26]. A strategy that combines relief of anatomic obstruction in the Fontan pathway and vigorous pulmonary vasodilation with catheter-based occlusion of well-mapped, isolated sites of lymphatic leakage into the airways may ultimately be the ideal management plan.…”
Section: Commentmentioning
confidence: 99%